The prevalence and causes of visual impairment among eye clinic patients at Nkhensani Hospital, Limpopo Province, South Africa - Maake, Modjadji Margareth (My University, 2015)
Purpose: The purpose of this study was to determine the prevalence and causes of visual impairment (low vision and blindness) among eye clinic patients at Nkhensani hospital in Limpopo province, South Africa. Methods: This was a cross sectional design in which 400 stratified participants aged ≥ 6 years were selected {100 participants in each stratum (6 – 18; 19 – 35; 36 – 59 and ≥ 60 years)}. Presenting, pinhole and best corrected visual acuities were measured using a logMAR E chart. Where reduced visual acuity (VA) was due to uncorrected refractive errors (UREs), ophthalmic lenses were used to compensate for the refractive errors using subjective refraction method and best corrected VA was measured. All participants underwent external and internal ocular examinations using ophthalmoscope to detect eye diseases. Participants with ocular pathology were referred to the ophthalmic nurse and/or ophthalmologist for further management. Refractive error findings were elaborated on in this study in order to highlight the importance and impact of this eye condition. Results: The ages of participants ranged from 6 to 92 years with mean of 39.5 ± 23.5 years. They included 161 (40.3%) males and 239 (59.8%) females. The prevalence of significant visual impairment (SVI) (VA < 6/18 to no light perception, i.e. low vision and blindness), low vision and blindness based on presenting visual acuity (PVA) in the right eye were 34.8%, 16.3% and 18.5% respectively while the prevalence based on the best corrected VA were 24.0%, 7.5% and 16.5% respectively. Based on the PVA, there was a significant association between age (Chi = 71.6; df =3; p = 0.00) and gender (Chi = 8.9; df =1; p = 0.003) with visual impairment (VI) of the right eye. In the left eye, the prevalence of SVI, low vision and blindness based on PVA were 35.8%, 17.5% and 18.3% respectively, while the prevalence based on best corrected VA were 24.8%, 8.5% and 16.3% respectively. Based on PVA, there was a significant association between age and visual impairment in the left eye (Chi = 52.9; df =3; p = 0.00) but there was no association between gender and VI (Chi = 1.9; df =1; p = 0.163). In both eyes, the prevalence of SVI, low vision and blindness based on PVA were 27.0%, 17.5% and 10.3% respectively, while the prevalence based on best corrected VA were 16.8%, 3.8% and 9.5% respectively. Based on the PVA, there was a significant association between age and VI (Chi = 54.1; df =3; p = 0.00) and gender and VI (Chi = 4.7; df =1; p = 0.03) in both eyes. iv The causes of significant visual impairment were uncorrected refractive errors (38.0%), cataract (25.9%) and glaucoma (17.6%) in both eyes. Among all participants, the leading causes of low vision based on presenting VA were uncorrected refractive errors (56.7%), cataract (20.9%) and glaucoma (9.0%). The main causes of blindness in both eyes were cataract (34.1%), glaucoma (31.7%) and corneal anomalies (17.1%) based on presenting visual acuity. After optical corrections, the main causes of VI were cataract (39.4%), glaucoma (28.8%) and corneal anomalies (18.2%). The main causes of low vision were cataract (42.9%), glaucoma (21.4%) and corneal anomalies (17.9%), while the main causes of blindness were cataract (39.5%), glaucoma (34.2%) and corneal anomalies (15.8%). Conclusion: The findings in this study indicate that the overall prevalence of visual impairment, low vision and blindness among patients attending the Nkhensani hospital eye clinic were 27.0%, 16.8% and 10.3% respectively. The main causes of visual impairment, low vision and blindness were uncorrected refractive errors, cataract and glaucoma. A focus on the optical correction of refractive errors and surgical intervention in the case of cataract would lead to a significant reduction in the burden of visual impairment among patients who utilise Nkhensani hospital for eye care services. Also, early detection and appropriate management of glaucoma will reduce the burden of this ocular morbidity. A significant proportion of these prevailing ocular morbidities are avoidable and with appropriate management, visual impairment is preventable.
Thesis (MPH.) -- University of Limpopo, 2015
Keywords: Visual impairment; Vision disorders.; Low vision -- Patients; People with visual disabilities.